Penggunaan Metode Pembelajaran Ability Grouping dalam Meningkatkan Kualitas Bacaan Al-Qur’an Santri Berdasarkan Tajwid dan Kelancaran Makhroj Huruf - Sulthon El Hasbi Rambe; Erawadi Erawadi; Hamdan Hasibuan (Lentera Ilmu: Jurnal Kependidikan, Riset dan Teoritis, 2025)
The Qur'an learning process at Darul Huffadh Islamic Boarding School, Gunung Tua, Padang Bolak, North Padang Lawas Regency, still uses traditional teaching methods that overlook students’ varying abilities, particularly in tajwid and makhraj. This lack of adaptive instruction lowers reading quality and student motivation. This study used Classroom Action Research (CAR) over two cycles, involving planning, implementation, observation, and reflection. Data were collected through observation, tests, interviews, and documentation. The results showed that implementing the Ability Grouping method significantly improved students’ Qur'an reading skills, especially in tajwid and pronunciation accuracy. Students in homogeneous groups felt more confident and motivated, as the instruction matched their learning needs. Thus, Ability Grouping proved to be an effective and relevant method for Qur'an learning in the pesantren setting.